Relationship between Radiological Severity, Knee Pain and Functional Limitation in Patients With Knee Osteoarthritis at Dr. M. Djamil Padang General Hospital - Yona Riapesi; Rizki Rahmadian; Hendra Maska (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2021)
Background: Osteoarthritis (OA) is a degenerative joint disease frequently affecting the elderly and the middle class due to injury or overuse of the joints. An individual with pain due to OA will experience dysfunction of joints and muscles, thus causing movement limitation, decrease of muscle strength and balance. The objective of this study is to know the association of OA radiological degree with pain intensity and limitation of physical capability in patients with knee joint OA. Methods: This study is a retrospective study on patients with knee joint OA treated at RSUP Dr. M. Djamil Padang in year 2021 from January 2021 to May 2021. Data collection was conducted in the Medical Records Department of RSUP Dr. M. Djamil Padang and questionnaire which fulfills the inclusion and exclusion criteria. Results: A total of 58 patients fulfilled the inclusion criteria of this study. Results of the study showed the mean age of the respondents was 60 years with variance of 7 years. More than a half (77.6%) of the respondents were female and most common ethnicity was Minang (82.8%). 50% of the patients were housewives. BMI of the respondents were mostly overweight - obese (65.5%). Most commonly affected side of the knee joint OA was the right side (55.2%). Most common degree of OA was the fourth degree (39.7%). More than a half of the respondents (84.5%) had moderate intensity of pain and 34.5% respondents had mild physical limitation. Results of the study showed that there was an association between OA radiological degree and pain intensity in patients with knee joint OA (p value = 0.0001). Results of the study showed that there was an association between OA radiological degree and level of physical capability limitations in patients with knee joint OA (p value = 0.0001). Results of the study showed that there was an association between pain intensity and level of physical capability limitations in patients with knee joint OA (p value = 0.0001). Conclusion: There was an association between OA radiological degree and pain intensity, physical limitations in patients with knee joint OA, and there was an association between pain intensity and level of physical capability limitation in patients with knee joint OA.